Peningkatan Kemampuan Motorik Halus pada Siswa Retardasi Mental - Dewi Mayangsari (Universitas Trunojoyo Madura, 2014)
Every child has the right to education and teaching in the context of personal development and the level of intelligence in accordance with their interests and latents, whereearly childhood is a time of preparation of the child to gain higher knowledge. When making observations and preliminary interviews as TK, there is one student whoTK A experiencing a fundamental difficulty is writing. After being given a series of tests, observations and interviews the results of the students have difficulty writing due to poor fine motor skills are developmentally appropriate and cognitive abilities including mild mental retardation category. Then, the students are given a fine motor skill development activites during meetings. The result is an increase in the fine motor skills in students.